2018
DOI: 10.1177/0267659118808728
|View full text |Cite
|
Sign up to set email alerts
|

Gender and intraoperative blood transfusion: analysis of 54,122 non-reoperative coronary revascularization procedures

Abstract: Background: Previous studies have shown that women undergoing isolated coronary artery bypass graft (CABG) surgery have an increased risk for postoperative morbidity and mortality when compared to men. Additionally, recent evidence suggests that blood transfusions are independently associated with an increased risk of adverse outcome. Methods: We evaluated gender differences in the risk of intraoperative red blood cell (RBC) transfusion during CABG surgery. Consecutive, non-reoperative CABG procedures performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Female patients were more likely to receive intraoperative blood transfusion than male patients. A study by Stammers involved 54,122 blood transfusion patients and exhibited that the rate of blood transfusion in female patients was almost three times higher than that in male patients, [ 13 ]. This finding is concurrent with that of Cao et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female patients were more likely to receive intraoperative blood transfusion than male patients. A study by Stammers involved 54,122 blood transfusion patients and exhibited that the rate of blood transfusion in female patients was almost three times higher than that in male patients, [ 13 ]. This finding is concurrent with that of Cao et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The delay in surgery due to inadequate preoperative blood preparation is deleterious for patients. The requirement for blood transfusion in spinal tuberculosis surgery depends on several factors such as anaemia caused due to a deficiency of iron [ 11 ], vitamin B12, and folic acid [ 12 ], which are used to compound haemoglobin (HGB) and sex of the patient [ 13 15 ]. Dong et al exhibited that the factors such as preoperative mean corpuscular haemoglobin concentration, surgical duration, preoperative HGB, intraoperative blood loss, number of fused vertebrae, and anticoagulant history can predict the risk of blood transfusion after spinal tuberculosis fusion [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Female sex has been associated with an increased rate of blood transfusion in cardiac and major non-cardiac surgery [36][37][38]. Furthermore, Siegrist et al found in a large cystectomy cohort that blood loss and transfusion rate were higher in 280 females [39].…”
Section: Discussionmentioning
confidence: 99%
“…[7,21,25,32] A recent study reported that female patients had a higher risk of intraoperative blood transfusion than male patients because of sex differences in preoperative hematocrit and blood volume. [33] DM is related to coagulopathy, microvasculopathy, and a hypercoagulable state, [34,35] which may increase the risk of intraoperative blood transfusions. CAD is associated with anticoagulants and, therefore, increases the risk of surgical bleeding.…”
Section: Discussionmentioning
confidence: 99%